2015
DOI: 10.1002/jor.22944
|View full text |Cite
|
Sign up to set email alerts
|

Genetic loci that regulate ectopic calcification in response to knee trauma in LG/J by SM/J advanced intercross mice

Abstract: This study reports on genetic susceptibility to ectopic calcification in the LG/J and SM/J advanced intercross mice. Using 347 mice in 98 full-sibships, destabilization of medial meniscus (DMM) was performed to induce joint injury. We performed quantitative trait locus (QTL) analysis to map ectopic calcification phenotypes to discrete genomic locations. To validate the functional significance of the selected QTL candidate genes, we compared mRNA expression between parental LG/J and SM/J inbred strains. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 56 publications
4
40
0
Order By: Relevance
“…In order to examine strain‐specific gene expression in response to DMM surgery, we used material from the histology slides to probe a panel of 78 candidate genes compiled previously for our work on ectopic calcifications and cartilage repair . The list of candidate genes is in Supplementary Table 2, http://onlinelibrary.wiley.com/doi/10.1002/art.40730/abstract.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to examine strain‐specific gene expression in response to DMM surgery, we used material from the histology slides to probe a panel of 78 candidate genes compiled previously for our work on ectopic calcifications and cartilage repair . The list of candidate genes is in Supplementary Table 2, http://onlinelibrary.wiley.com/doi/10.1002/art.40730/abstract.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that mice develop ectopic calcifications (i.e., calcified nodules in and around the synovium) after surgical DMM or mechanical loading . In the present study, we quantified these nodules after joints were scanned by micro‐CT scanner as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…Although we have shown that synovitis and cartilage degeneration are uncoupled23, others have suggested their co-occurrence53. We have recently shown that ectopic calcification has a strong genetic component to it as evidenced by identification of quantitative trait loci in the advanced intercross population of LG/J and SM/J54. Using LG/J, SM/J and their advanced intercross, we previously discovered that joint destabilization instigates meniscal and synovial ectopic calcification54.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that ectopic calcification has a strong genetic component to it as evidenced by identification of quantitative trait loci in the advanced intercross population of LG/J and SM/J54. Using LG/J, SM/J and their advanced intercross, we previously discovered that joint destabilization instigates meniscal and synovial ectopic calcification54. Interestingly, we observed the same phenotype in loaded knees and more so in the knees with ACL tear (data not shown), thus strengthening our hypothesis, that calcification occurs in unstable joints.…”
Section: Discussionmentioning
confidence: 99%
“…For heritability studies, the use of inbred strains is preferred because any phenotypic variation detected is due to different combinations of each parental genome without the confounding influence of different genetic backgrounds that outbred strains would have [59]. These LG/J and SM/J inbred strains have been studied for a range of complex musculoskeletal phenotypes including ectopic calcification [60], long bone growth, mechanical properties [61] and muscle weight [62]. …”
Section: Mapping the Articular Cartilage Healing Traitmentioning
confidence: 99%